Board composition, institutional ownership, firm performance and Islamic corporate social responsibility (ICSR) disclosure / Muhammad Mukhlis Abdul Fatah - Abdul Fatah, Muhammad Mukhlis (2012)
Recently, there is a growing concern especially among muslims society to opt to the fully-fledged Islamic banks as an alternative to the conventional banks due to the requirement of shari'ah. Malaysia as one of the leading Islamic country that continuously emphasise on the Islamisation process has been selected as the focus of the study. The fully-fledged Islamic banks in Malaysia have adopted the Islamic corporate social responsibility (ICSR) disclosure in their daily practices which will reflect the interest of the muslims stakeholders and other stakeholders. The study examines factors that determine the Islamic corporate social responsibility (ICSR) disclosure based on two theories i.e. resource-based theory and stakeholders' theory. Based on resource-based theory, this study examines the influence of five largest institutional ownership, muslims board members, top management support and the independent non-executive directors on the ICSR disclosure. In addition, the effects of the ICSR disclosure to the firm performance based on stakeholders' theory are also examined. Furthermore, the content analysis is used to measure the extent of ICSR disclosure with the related variables based on the annual reports of the 17 fully-fledged Islamic banks in Malaysia for the year ended 2008 until 2010. The findings of the study shows that muslims board members and top management support significantly influence the ICSR disclosure while the independent non-executive directors do not influence the ICSR disclosure. On other hand, five largest shareholders have inverse relationship with the ICSR disclosure. Furthermore, ICSR disclosure is significantly affecting the Islamic banks' performance which is in line with the stakeholders' theory. Thus, ICSR disclosure is viewed as intangible resources as well as can be used as important strategy which improves the Islamic banks profitability besides portrays good reputation to public. Overall, this study highlights the importance of board composition, top management support and the institutional ownership on the ICSR disclosure. Further, ICSR influence Islamic banks to disclose more ICSR information in annual reports and subsequently improving the firm performance.